Influencing Factors of Academic Entrepreneurship-Based Knowledge Mapping: A Comparative Analysis of Chinese and International Literature - Liu Ziyu; Zhao Lixia (Discrete Dynamics in Nature and Society)
In order to analyze the hot frontier of academic entrepreneurship and study the influencing factors of academic entrepreneurship, By using citespace V information visualization software and content analysis, 32 papers in CNKI (China National Knowledge Infrastructure) database are retrieved which are indexed by CSSCI (Chinese Social Sciences Citation Index), and 66 papers are retrieved in Web of Science database which are indexed by SSCI (Social Sciences Citation Index); the Chinese and international sample papers were compared and analyzed, and a comparative analysis between Chinese and international papers was made. The results show that the influencing factors of academic entrepreneurship are divided into personal, environmental, and organizational factors. There are many researches on personal factors in China and external factors such as environment, organization, and system in international countries. Chinese research tends to the macrolevel, while international research pays more attention to the microlevel. The research frontier at home and abroad is the research of academic entrepreneurial process at microlevel. Finally, some suggestions are given to academic entrepreneurship: academic exchanges should be strengthened, more support platforms should be set up in university institutions, and the state should introduce incentive policies to enhance the strength and level of academic entrepreneurship.